Association of plasminogen activator inhibitor-1 and tissue plasminogen activator with type 2 diabetes and metabolic syndrome in Malaysian subjects - Al-Hamodi, Z.; Ismail, I.S.; Saif-Ali, R.; Ahmed, K.A.; Muniandy, S. (2011)
Background: Increased plasma plasminogen activator inhibitor-1 (PAI-1) activity and decreased tissue plasminogen activator (tPA) activity could be considered a true component of the metabolic syndrome (MetS) associated with an increased risk of developing cardiovascular diseases (CVD) and fibrinolytic abnormalities. The aim of this study was to investigate the association of tPA and its inhibitor PAI-1 with type 2 diabetes (T2D) and MetS and interrelationship between PAI-1 and tPA activities and antigens in Malaysian T2D and normal subjects. Methods: The plasma activities and antigens of PAI-1 and tPA and the levels of the tPA/PAI-1 complex as well as serum insulin, parameter of the coronary risk panel and plasma glucose at fasting state were studied in 303 T2D subjects (227 with MetS and 76 without MetS), 131 normal non-diabetic non-metabolic subjects and 101 nondiabetic MetS subjects. Results: The PAI-1 activity was higher in subjects with T2D with MetS (P = 9.8 x 10(-19)) and non-diabetic subjects with MetS (P = 3.0 x 10(-15)), whereas the tPA activity was lower in T2D with MetS (P = 0.003) as compare to normal subjects. Plasma tPA antigen levels were higher in subjects with T2D with MetS (P = 8.9 x 10(-24)), T2D without MetS (P = 1.3 x 10(-13)) and non-diabetic MetS subjects (P = 0.002). The activity and antigen of PAI-1 in normal subjects were related to insulin resistance (P = 2.2 x 10(-4); 0.007). Additionally, the PAI-1 activity was associated with an increased waist circumference (P = 2.2 x 10(-4)) and decreased HDL-c (P = 0.005), whereas the tPA activity was associated with decreased FBG (P = 0.028). The highest correlation was between PAI-1 activity and its antigen (R(2) = 0.695, P = 1.1 x 10(-36)) in diabetic subjects. The tPA activity negatively correlated with its antigen (R(2) = -0.444, P = 7.7 x 10(-13)) in normal subjects and with the PAI-1 activity and antigen (R(2) = -0.319, P = 9.9 x 10(-12); R2 = -0.228, P = 3.4 x 10(-6)) in diabetic subjects. Conclusions: PAI-1 and tPA activities and antigens were associated with diabetes and MetS parameters in Malaysian subjects.